Bile acids in Alzheimer’s disease: a double-edged sword in gut–liver–brain signaling and neurodegeneration - Rehana Basri; Hayder M. Al-kuraishy; Mubarak Alruwaili; Ali I. Al-Gareeb; Ali K. Albuhadily; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Gaber El-Saber Batiha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder characterized by amyloid-β (Aβ) deposition, tau pathology, synaptic dysfunction, neuroinflammation, and metabolic impairment. Increasing evidence suggests that bile acids, traditionally recognized for their roles in lipid digestion and hepatic metabolism, act as endocrine signaling molecules that influence central nervous system (CNS) homeostasis. Through enterohepatic circulation and microbiota-dependent biotransformation, bile acid composition is dynamically regulated and can modulate peripheral metabolic and immune pathways with downstream effects on the brain. Notably, bile acid signaling via key receptors such as the farnesoid X receptor (FXR) and the Takeda G protein-coupled receptor 5 and G-protein-coupled bile acid receptor 1 (TGR5/GPBAR1) has emerged as a mechanistic bridge linking liver–gut physiology to neuroinflammatory and neurodegenerative processes. Altered bile acid profiles have been reported in AD and mild cognitive impairment, with accumulating findings suggesting that hydrophobic secondary bile acids may contribute to blood–brain barrier (BBB) disruption and neurotoxicity. In contrast, hydrophilic bile acids may exert neuroprotective and anti-inflammatory effects. In addition, bile acids drive the release of gut hormones such as glucagon-like peptide 1 (GLP-1) and fibroblast growth factor 19 (FGF19), highlighting indirect neurometabolic pathways relevant to cognition and neurodegeneration. This narrative review synthesizes current biochemical, experimental, and clinical evidence supporting a role for bile acid signaling in AD pathogenesis and progression. We discuss receptor-mediated pathways, microbiota-bile acid interactions, neuroimmune modulation, and translational perspectives, proposing that bile acid–based biomarkers and therapeutic strategies targeting FXR/TGR5 signaling may represent promising avenues for future AD intervention.

Targeting of MAPK–ERK1/2 signaling by metformin in asthma: an updated mechanistic insight - Manal Ewaiss Hassan; Hayder M. Al-kuraishy; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Eman K. Rashwan; Gaber El-Saber Batiha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Asthma is a heterogeneous chronic inflammatory airway disease characterized by persistent inflammation, dysregulated immune signaling, and progressive airway remodeling. It has been shown that asthma pathogenesis involves multiple signaling pathways. It has been illustrated that the mitogen-activated protein kinase/extracellular signal-regulated kinase 1/2 (MAPK/ERK1/2) cascade, which emerges as a central regulator linking immune activation, epithelial dysfunction, and structural remodeling of the airway, is implicated in the pathogenesis of asthma. Sustained ERK1/2 activation is consistently demonstrated in human asthmatic airways and experimental models, correlating with disease severity, inflammatory cell infiltration, and corticosteroid resistance. This review provides a comprehensive and critical discussion of the ERK1/2 signaling in asthma, spanning immune cells, airway epithelium, and airway smooth muscle. We evaluate preclinical and translational evidence supporting ERK1/2 as a therapeutic target and examine emerging pharmacological strategies, including indirect pathway modulation via AMP-activated protein kinase (AMPK) activation and drug repositioning with the anti-diabetic metformin. By integrating mechanistic insights with therapeutic implications, this review positions ERK1/2 as a pivotal signaling node for precision targeting in severe, treatment-refractory asthma.

Phosphodiesterase signaling in asthma: mechanistic insights and emerging therapeutic strategies - Abdulelah Alnusayri; Hayder M. Al-kuraishy; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Mubarak Alruwaili; Gaber El-Saber Batiha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Asthma is a clinically and biologically heterogeneous disease for which current anti-inflammatory therapies, including inhaled corticosteroids, remain insufficient for many patients. Therefore, repurposing other FDA-approved drugs, such as phosphodiesterase (PDE) inhibitors, may be beneficial in the management of asthma. PDEs are central regulators of cyclic nucleotide signaling, modulating airway smooth-muscle tone, mucociliary function, and immune-cell activity by compartmentalizing the control of cAMP and cGMP. Although PDE4 inhibitors have shown strong pre-clinical efficacy, their translation into clinical practice has been hindered by dose-limiting systemic toxicities, revealing a persistent gap between mechanistic promise and therapeutic utility. This review synthesizes emerging insights into PDE isoenzyme selectivity, spatial localization, and cross-regulatory interactions across structural and immunocompetent airway cells. We outline how isoform- and splice-variant–specific functions contribute to key asthmatic phenotypes and evaluate innovative therapeutic strategies, including dual PDE3/4 inhibition, inhaled delivery approaches, and next-generation selective modulators designed to overcome historical limitations. By integrating these advances within an endotype-driven precision-medicine framework, this review provides a path toward unlocking the full therapeutic potential of PDE-targeted interventions in asthma.

Placental dysfunction, inflammation, and impaired autophagy in preeclampsia: A pathophysiological link to autism spectrum disorder - Anass M. Abbas; Hayder M. Al-kuraishy; Al-Maiahy. Thabat J; Ali I. Al-Gareeb; Aya M. Mustafa; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Metabolic Brain Disease, 2026)

SIRT1 Activators as Geroprotective Agents in Brain Aging: Mechanisms and Therapeutic Potential - Ayman Ali Mohammed Alameen; Hayder M. Al-Kuraishy; Ali I. Al-Gareeb; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Gaber El-Saber Batiha (NeuroMolecular Medicine, 2026)
The brain undergoes profound molecular and structural changes during the aging process, resulting in the development of neurodegeneration, cognitive impairment, and increased vulnerability to chronic diseases. At the cellular level, brain aging is characterized by oxidative damage, genomic instability, and chronic low-grade inflammation known as inflammaging. Central to this process is Sirtuin 1 (SIRT1), a NAD + -dependent class III histone deacetylase, known for its regulatory role in chromatin remodeling, oxidative stress responses, mitochondrial biogenesis, and neuroplasticity. Recent research has identified SIRT1 as a molecular target capable of reversing or attenuating several hallmarks of aging, particularly within the central nervous system (CNS). This narrative review critically evaluates the emerging evidence surrounding the geroprotective effects of SIRT1 activators, which exert dual actions, senomorphic and senolytic, via modulation of signaling pathways, thereby reducing neuronal senescence, enhancing autophagy, and mitigating inflammatory responses. The discussion also addresses the region-specific role of SIRT1 across the brain, particularly in the hippocampus and hypothalamus, which are essential for memory, energy homeostasis, and resilience to stress. Additionally, this review explores how SIRT1 depletion during aging contributes to the development of synaptic dysfunction, impaired cognitive function, and susceptibility to neurodegenerative diseases such as Alzheimer’s disease (AD) and Parkinson’s disease (PD). The therapeutic potential of SIRT1 activators is supported by preclinical and early clinical studies, suggesting their value in preventing or delaying brain aging. Thus, SIRT1 could be a promising pharmacological target for age-associated brain disorders, warranting more robust translational studies to validate these findings in humans.

The potential role of adenosinergic pathway and methylxanthines in Parkinson’s disease: Blowing in the wind or not - Alaa Ismail; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Luay M. Alkazmi; Abdullah Faisal Albukhari; Mustafa M. Shokr; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Purinergic Signalling, 2026)

Role of insulin-like growth factor-1/2 and related signaling in parkinson’s disease - Emad Manni; Hayder M. Al-kuraishy; Thabat J. Al-Maiahy; Ali I. Al-Gareeb; Mustafa M. Shokr; Athanasios Alexiou; Marios Papadakis; Shaimaa M Hassan; Gaber El-Saber Batiha (Metabolic Brain Disease, 2026)

Emerging contaminants and their influence on plants: An in-depth review - Sadia Aziz; Sania Zaib; Azhar Iqbal; Muhammad Asif Chuadhry; Shaheen Shahzad; Bikram Dhara; Athanasios Alexiou; Partha Biswas; Mohamed M. Abdel-Daim; Shabana Bibi (Environmental Toxicology and Pharmacology, 2026)

Unveiling the Neuroprotective Effect of Paraoxonase 1 in Neurodegenerative Diseases Focusing on Alzheimer’s Disease - Alaa Ismail; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Athanasios Alexiou; Marios Papadakis; Safaa A. Faheem; Gaber El-Saber Batiha (Molecular Neurobiology, 2026)

Metformin as a Neuroendocrine Modulator in Catamenial Epilepsy: Interplay with Sex Hormones and Neurosteroids - Ayman Ali Mohammed Alameen; Hayder M. Al-kuraishy; Thabat J. Al-Maiahy; Ali I. Al-Gareeb; Aya M. Mustafa; Abdullah Faisal Albukhari; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Molecular Neurobiology, 2026)

SARS-CoV-2 infection and gut-lung axis: the potential role of rifaximin - Taghreed N. Almanaa; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Maii A. Abdelnaby; Athanasios Alexiou; Marios Papadakis; Islam E. Abo-ElFetoh; Gaber El-Saber Batiha (Inflammopharmacology, 2026)

Pharmacological modulation of the PI3K/AKT/GSK3β axis: a new frontier in Alzheimer’s disease treatment - Saad Misfer Alqahtani; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Mustafa M. Shokr; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Inflammopharmacology, 2026)

Drug repositioning as a promising approach for the eradication of emerging and re-emerging viral agents - Marwa Almulhim; Abdolmajid Ghasemian; Mojtaba Memariani; Farnaz Karami; Asmaa S. A. Yassen; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Molecular Diversity, 2025)
The global impact of emerging and re-emerging viral agents during epidemics and pandemics leads to serious health and economic burdens. Among the major emerging or re-emerging viruses include SARS-CoV-2, Ebola virus (EBOV), Monkeypox virus (Mpox), Hepatitis viruses, Zika virus, Avian flu, Influenza virus, Chikungunya virus (CHIKV), Dengue fever virus (DENV), West Nile virus, Rhabdovirus, Sandfly fever virus, Crimean-Congo hemorrhagic fever (CCHF) virus, and Rift Valley fever virus (RVFV). A comprehensive literature search was performed to identify existing studies, clinical trials, and reviews that discuss drug repositioning strategies for the treatment of emerging and re-emerging viral infections using databases, such as PubMed, Scholar Google, Scopus, and Web of Science. By utilizing drug repositioning, pharmaceutical companies can take advantage of a cost-effective, accelerated, and effective strategy, which in turn leads to the discovery of innovative treatment options for patients. In light of antiviral drug resistance and the high costs of developing novel antivirals, drug repositioning holds great promise for more rapid substitution of approved drugs. Main repositioned drugs have included chloroquine, ivermectin, dexamethasone, Baricitinib, tocilizumab, Mab114 (Ebanga™), ZMapp (pharming), Artesunate, imiquimod, saquinavir, capmatinib, naldemedine, Trametinib, statins, celecoxib, naproxen, metformin, ruxolitinib, nitazoxanide, gemcitabine, Dorzolamide, Midodrine, Diltiazem, zinc acetate, suramin, 5-fluorouracil, quinine, minocycline, trifluoperazine, paracetamol, berbamine, Nifedipine, and chlorpromazine. This succinct review will delve into the topic of repositioned drugs that have been utilized to combat emerging and re-emerging viral pathogens.

Interconnection between myasthenia gravis and type 2 diabetes: emerging role of metformin in modulating PI3K/AKT/mTOR/AMPK axis - Ahmed salem Al-Dhahi; Hayder M. Al-Kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Aya M. Mustafa; Alaa Ismail; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Metabolic Brain Disease, 2025)

The AMPK/GDF15 Axis: A Novel Target for the Neuroprotective Effects of Metformin in Ischemic Stroke - Ghadah H. Alshehri; Hayder M. Al-kuraishy; Bshra A. Alsfouk; Ali I. Al-Gareeb; Safaa A. Faheem; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Molecular Neurobiology, 2025)
Metformin is an anti-diabetic drug used in the management of type 2 diabetes (T2D). Metformin has different pleiotropic effects, such as anti-inflammatory, antioxidant, antithrombotic, and vasculoprotective. Metformin has neuroprotective effects against neurodegenerative diseases and ischemic stroke. Conversely, metformin may exacerbate the pathogenesis of ischemic stroke. This controversial point may be related to the impact of metformin on the different signaling pathways, such as AMP-activated protein kinase (AMPK) and growth differentiation factor 15 (GDF-15). Many studies have reported the effect of metformin on ischemic stroke, with AMPK signaling only. However, little has been explored about the impact of metformin on the GDF-15 signaling in ischemic stroke. Accordingly, this review aims to discuss the role of metformin in the neuropathology of ischemic stroke regarding the AMPK and GDF-15 signaling pathways.

Targeting of the PI3 K/AKT/GSK3β Pathway in Parkinson's Disease: A Therapeutic Blueprint - Raed AlRuwaili; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Athanasios Alexiou; Marios Papadakis; Mohammed E. Abo-El Fetoh; Gaber El-Saber Batiha (Molecular Neurobiology, 2025)
Parkinson's disease (PD) is a neurodegenerative disease characterized by progressive motor and non-motor symptoms. PD neuropathology is due to the progressive deposition of mutant alpha-synuclein (α-Syn) in the dopaminergic neurons of the substantia nigra pars compacta (SNpc). This effect initiates oxidative stress, mitochondrial dysfunction, inflammation, and apoptosis of the dopaminergic neurons in the SNpc. PD neuropathology, which is closely associated with inflammatory and oxidative disorders, disrupts different vital cellular pathways. Notably, the current anti-PD medications only relieve the symptoms of PD without averting the underlying neuropathology. Thus, it is advisable to search for novel drugs that attenuate the progression of PD neuropathology. It has been shown that phosphatidylinositol 3-kinase (PI3K), AKT, and glycogen synthase kinase 3 beta (GSK3β) signaling pathways are affected in PD. PI3K/AKT pathway is neuroprotective against the development and progression of PD. However, the over-activated GSK3β signaling pathway has a detrimental effect on PD neuropathology by inducing inflammation and oxidative stress. Dysregulation of the PI3K/AKT/GSK3β signaling pathway provokes brain insulin resistance (BIR), neuroinflammation, and neuronal apoptosis, the hallmarks of PD and other neurodegenerative diseases. However, the mechanistic role of the PI3K/AKT/GSK3β signaling pathway is not fully clarified. Therefore, in this review, we intend to discuss the role of the PI3K/AKT/GSK3β signaling pathway in PD pathogenesis and how PI3K/AKT activators and GSK3β inhibitors have helped effectively manage PD.

Enterogenic dementia: defining the gut–brain axis and the role of inflammatory bowel disease in cognitive impairment - Faisal Alshammari; Hayder M. Al-Kuraishy; Mustafa M. Shokr; Marios Papadakis; Athanasios Alexiou; Gaber El-Saber Batiha (Inflammopharmacology, 2025)

Moniezia benedeni infected Zaraibi (Egyptian Nubian) goats: Insights into serum biochemical changes, redox imbalance, and molecular mechanisms of oxidative-inflammatory cascades mediated intestinal injury - Mahmoud Abdelhamid; Ahmed Magdy Selim; Ragab Hassan Mohamed; Rasha Salah Mohamed; Ahmed Ateya; Suad Hamdan Almasoudi; Athanasios Alexiou; Marios Papadakis; Ahmed M. El-Sebaey (Research in Veterinary Science, 2025)

The potential role of carvedilol in COVID-19 management: perspective and take-away - Hayder M. Al-Kuraishy; Maii A. Abdelnaby; Marios Papadakis; Athanasios Alexiou; Gaber El-Saber Batiha (Inflammopharmacology, 2025)

Tirzepatide: a novel therapeutic approach for Alzheimer’s disease - Ghadah H. Alshehri; Hayder M. Al-kuraishy; Huda Jaber Waheed; Ali I. Al-Gareeb; Safaa A. Faheem; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Metabolic Brain Disease, 2025)
Tirzepatide (TRZ) is a dual agonist of glucagon-like peptide 1 (GLP-1) and gastric inhibitory polypeptide (GIP) receptors that were recently approved for the treatment of type 2 diabetes (T2D) and obesity. Of note is that T2D and obesity, by inducing peripheral low-grade inflammation and oxidative stress, provoke the development of central neuroinflammation and oxidative stress. Together, T2D and obesity are regarded as potential risk factors implicated in the development and progression of Alzheimer’s disease (AD), which is the most common neurodegenerative disease and represents the most typical cause of dementia. Hence, targeting low-grade inflammation and oxidative stress in T2D and obesity by TRZ may reduce AD neuropathology. In addition, TRZ can inhibit the production of amyloid beta (Aβ) and associated neuroinflammation, oxidative stress, and neuronal apoptosis. However, the underlying neuroprotective mechanism of TRZ against AD is not entirely explained. Consequently, this mini-review aims to discuss the possible molecular mechanism of TRZ in AD.

Paracetamol: the potential therapeutic pathways defining its clinical use - Hayder M. Al-Kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Eman M. Abd El-maksoud; Mustafa M. Shokr; Athanasios Alexiou; Marios Papadakis; Gaber El-Saber Batiha (Inflammopharmacology, 2025)

Unlocking Alzheimer’s Disease: The Role of BDNF Signaling in Neuropathology and Treatment - Saad Misfer Alqahtani; Hayder M. Al-kuraishy; Ali I. Al Gareeb; Ali K. Albuhadily; Athanasios Alexiou; Marios Papadakis; Loah R. Hemeda; Safaa A. Faheem; Gaber El-Saber Batiha (NeuroMolecular Medicine, 2025)
Alzheimer’s disease (AD) remains one of the most debilitating neurodegenerative disorders, with its pathological hallmark being progressive cognitive decline and memory loss. Recent research has illuminated the crucial role of the brain-derived neurotrophic factor (BDNF) in the central nervous system (CNS), highlighting its impact on neurogenesis, synaptic plasticity, and neuronal survival. Dysregulation of the BDNF signaling axis, particularly the imbalance between its precursor form and mature BDNF, is strongly implicated in the pathophysiology of AD. This review explores the molecular mechanisms through which BDNF modulates AD neuropathology and presents novel therapeutic strategies to activate BDNF signaling. We focus on the potential of BDNF activators, such as TrkB agonists and mimetic molecules, to restore synaptic function and ameliorate cognitive deficits in AD. Furthermore, we examine the challenges in translating these findings into clinical practice, including issues with blood–brain barrier penetration and the need for precise receptor targeting. The review emphasizes the therapeutic potential of repurposed drugs, including statins and metformin, in enhancing BDNF signaling and offers new insights into the future of AD treatment. Ultimately, this work provides a compelling argument for BDNF-based therapies as a promising avenue for mitigating the cognitive decline associated with Alzheimer’s disease, signaling a hopeful direction for future research and clinical trials.

Retraction Note: COVID-19 diagnostic methods in developing countries - Md. Maniruzzaman; Md. Missile Islam; Md. Hazrat Ali; Nobendu Mukerjee; Swastika Maitra; Mohammad Amjad Kamal; Arabinda Ghosh; Melvin A. Castrosanto; Athanasios Alexiou; Ghulam Md. Ashraf; Priti Tagde; Md. Habibur Rahman (Environmental Science and Pollution Research, 2025)

The Conceivable Role of Metabolic Syndrome in the Pathogenesis of Alzheimer’s Disease: Cellular and Subcellular Alterations in Underpinning a Tale of Two - Ekremah A. Alzarea; Hayder M. Al-Kuraishy; Ali I. Al-Gareeb; Athanasios Alexiou; Marios Papadakis; Olivia N. Beshay; Gaber El-Saber Batiha (NeuroMolecular Medicine, 2025)
Alzheimer’s disease (AD)is an age-related neurodegenerative disease characterized by memory decline and cognitive impairment .AD is common in people aged > 65 years, though most of AD cases are sporadic, which accounts for 95%, and 1–5% of AD is caused by familial causes . The causes of AD are aging, environmental toxins, and cardiometabolic factors that induce the degeneration of cholinergic neurons. It has been shown that the metabolic syndrome which is a clustering of dissimilar constituents including insulin resistance (IR), glucose intolerance, visceral obesity, hypertension, and dyslipidemia is implicated in the pathogenesis of AD. Metabolic syndrome disapprovingly affects cognitive function and the development in AD by inducing the development of oxidative stress, neuroinflammation, and brain IR. These changes, together with brain IR, impair cerebrovascular reactivity causing cognitive impairment and dementia. Nevertheless, the fundamental mechanism by which metabolic syndrome persuades AD risk is not entirely explicated. Accordingly, this review aims to discuss the connotation between metabolic syndrome and AD. In conclusion, metabolic syndrome is regarded as a possible risk factor for the initiation of AD neuropathology by diverse signaling pathways such as brain IR, activation of inflammatory signaling pathways, neuroinflammation, defective proteostasis, and dysregulation of lipid mediators.

Temporal patterns and influences of monthly, seasonal and annual temperatures on methane emissions in Greece, Armenia and Russia over two decades - Abhishek Singh; Anil Kumar Singh; Sapna Rawat; Vishnu D. Rajput; Karen Ghazaryan; Vicky Anand; Tatiana Minkina; Athanasios Alexiou; Mohamed S. Elshikh; João Ricardo Sousa; Henrique Trindade; Rupesh Kumar Singh; et al. (Science of The Total Environment, 2025)

Eucalyptol attenuates indomethacin-induced gastric ulcers in rats by modulating the ICAM-1, eNOS and COX/LOX pathways: Insights from in silico, in vitro and in vivo approaches - Urooj Iqbal; Abdul Malik; Nabeela Tabassum Sial; Malik Hassan Mehmood; Ambreen Malik Uttra; Ume Ruqia Tulain; Alia Erum; Muhammad Fayyaz-ur-Rehman; Nermeen N. Welson; Mohamed H. Mahmoud; Athanasios Alexiou; Marios Papadakis; et al. (Food and Chemical Toxicology, 2025)

Editorial Expression of Concern to: The probable role of tissue plasminogen activator/neuroserpin axis in Alzheimer’s disease: a new perspective - Naif H. Ali; Hayder M. Al‑kuraishy; Ali I. Al‑Gareeb; Saud A. Alnaaim; Athanasios Alexiou; Marios Papadakis; Hebatallah M. Saad; Gaber El‑Saber Batiha (Acta Neurologica Belgica, 2025)

The Peripheral Amyloid-β Nexus: Connecting Alzheimer’s Disease with Atherosclerosis through Shared Pathophysiological Mechanisms - Manal M. Khowdiary; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Ahmed A. Elhenawy; Eman K. Rashwan; Athanasios Alexiou; Marios Papadakis; Mohammed E. Abo‑El Fetoh; Gaber El-Saber Batiha (NeuroMolecular Medicine, 2025)
Alzheimer’s disease (AD) and atherosclerosis (AS) are two chronic diseases with seemingly distinct pathologies. However, emerging research points to a bidirectional relationship driven by common mechanisms, such as inflammation, oxidative stress, and dysregulation of Amyloid-Beta (Aβ). This review focuses on the role of Aβ as a critical molecular link between AD and AS, emphasizing its contribution to neuronal impairment and vascular damage. Specifically, peripheral Aβ produced in the pancreas and skeletal muscle tissues exacerbates AS by promoting endothelial dysfunction and insulin resistance (IR). Furthermore, AS accelerates AD progression by impairing cerebral blood flow and inducing chronic hypoxia, causing Aβ accumulation. This review critically evaluates recent findings, highlighting inconsistencies in clinical studies and suggesting future research directions. Understanding the bidirectional influence of AD and AS could pave the way for novel therapeutic approaches targeting shared molecular pathways, particularly emphasizing Aβ clearance and inflammation.

Nutraceutical Impact of Pumpkin Seed Oil on Expression Levels of EZH-2 and KRT-14 Genes against DSS-induced Inflammatory Bowel Disease in the Rat Model - Asma Mukhtar; Imran Mukhtar; Humaira Muzaffar; Muhammad Naeem Faisal; Kashif ur rehman khan; Laaraib Nawaz; Muhammad Umar Ijaz; Sana Maryam; Muhammad Umair; Haseeb Anwar; Farid S. Ataya; Gaber El-Saber Batiha; et al. (Cell Biochemistry and Biophysics, 2025)
Inflammatory bowel disease is a collection of intestinal disorders that cause inflammation in the digestive tract. Prolonged inflammation in the gastrointestinal tract is a major risk factor for colorectal cancer. The objective of this study was to fucus on gene expression levels of ( KRT-14 ; associated with epithelial cell integrity) and enhancer of zeste homolog-1 ( EZH-2; involved in cellular proliferation) in a IBD rat model in order to rule out impact of nutraceuticals (pumpkin seed oil; PSO) as a complementary approach to conventional treatments of IBD. In the current study, IBD was induced using dextran sodium sulfate (DSS). Following acclimatization, rats were separated into three groups: the negative control, the positive control, and the treatment group. The DSS (1 ml/kg bw) was given to the positive control and treatment groups. Negative control was given only a normal diet. Pumpkin seed oil (PSO) was given orally as a treatment (0.5 ml/kg bw). Blood and colon tissue were obtained on the 5 th , 10 th , 14 th, and 18 th days. Physical parameters, hematology, biochemical assays, gene expression, and histopathology were carried out. After statistical analyses, macroscopic parameters showed significant differences. Biochemical analyses revealed a significant ( P ≤ 0.05) decrease in serum potassium concentrations, total cholesterol, triglycerides, total proteins, total oxidants status, and C-reactive proteins in PSO treated group as compared with positive control. Gene expression levels of KRT-14 and EZH2 were significantly ( P ≤ 0.05) upregulated in PSO treated group as compared to positive control group. Histopathology revealed that pumpkin seed oil preserved the structural integrity of colon.

Identification of novel phytotherapeutic agents for understanding hypertrophic cardiomyopathy via genetic mapping and advanced computational analysis - Abdullahi Tunde Aborode; Onifade Isreal Ayobami; Ammar Usman Danazumi; Christopher Busayo Olowosoke; Haruna Isiyaku Umar; Abraham Osinuga; Aeshah A. Awaji; Fatmah Ali Awaji; Ebenezer Ayomide Omojowolo; Najwa Ahmad Kuthi; Tanveer Shaikh; Babatunde Shuaib Anidu; et al. (Genome Instability & Disease, 2024)

β-Citronellol: a potential anti-inflammatory and gastro-protective agent-mechanistic insights into its modulatory effects on COX-II, 5-LOX, eNOS, and ICAM-1 pathways through in vitro, in vivo, in silico, and network pharmacology studies - Urooj Iqbal; Abdul Malik; Nabeela Tabassum Sial; Malik Hassan Mehmood; Shoaib Nawaz; Marios Papadakis; Dalia Fouad; Hayam Ateyya; Nermeen N. Welson; Athanasios Alexiou; Gaber El-Saber Batiha (Inflammopharmacology, 2024)
Background The current study aimed to evaluate the anti-inflammatory, anti-oxidant, and pronounced gastro-protective activities of β- Citronellol using in vitro , in vivo assays and in silico approaches. Methods In vitro assays, denaturation of bovine serum albumin, egg protein, and human Red Blood Cells (RBCs) membrane stabilization were performed, using Piroxicam as standard. For in vivo assessment, Histamine (0.1 ml from 1% w/v) and Formaldehyde (0.1 ml from 2% v/v) were used to mediate inflammation. In silico molecular docking and network pharmacology were employed to probe the possible target genes mediating gastroprotective effect of β-Citronellol at 25, 50, and 100 mg/kg, using indomethacin-induced (25 mg/kg i.p) gastric ulcer in rats. Moreover, Gastric tissues were evaluated for morphological, histopathological, and bio-chemical analysis of PGE 2, COX-I, COX-II, 5-LOX, eNOS, ICAM-1, oxygen-free radical scavengers (SOD, CAT), and oxidative stress marker (MDA). Results β - Citronellol prevented denaturation of proteins and RBCs membrane stabilization with maximum effect observed at 6,400 µg/mL. Citronellol decreased rat’s paw edema. Network pharmacology and docking studies revealed gastro-protective potential of Citronellol possibly mediated through arachidonic acid pathways by targeting COX-I, COX-II, PGE 2 , and 5-LOX. Citronellol reduced the ulcer indices, and histopathological changes. Further, β - Citronellol (50 and 100 mg/kg) increased gastric PGE 2, COX-1, and eNOS; while suppressing COX-2, 5-LOX and ICAM-1. Citronellol markedly enhanced the oxidative balance in isolated rat stomach tissues. Conclusions The anti-inflammatory, anti-oxidant, and gastro-protective effects of β - Citronellol against indomethacin-induced gastric ulcer model in rats through mediating COX-I, COX-II, PGE 2, 5-LOX, eNOS, and ICAM-1 inflammatory markers. Graphical abstract

Atheroprotective role of vinpocetine: an old drug with new indication - Mohammed H. Abu-Alghayth; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Athanasios Alexiou; Marios Papadakis; Mostafa M. Bahaa; Mohammed Afifi; Ammar AL-Farga; Eman Wahsh; Gaber El-Saber Batiha (Inflammopharmacology, 2024)
Endothelial dysfunction is considered one of the main causes of atherosclerosis and elevated blood pressure. Atherosclerosis (AS) formation is enhanced by different mechanisms including cytokine generation, vascular smooth muscle cell proliferation, and migration. One of the recent treatment toward endothelial dysfunction is vinpocetine (VPN). VPN is an ethyl apovincaminate used in the management of different cerebrovascular disorders and endothelial dysfunction through inhibition of atherosclerosis formation. VPN is a potent inhibitor of phosphodiesterase enzyme 1 (PDE1) as well it has anti-inflammatory and antioxidant effects through inhibition of the expression of nuclear factor kappa B (NF- κ B). VPN has been shown to be effective against development and progression of AS. However, the underlying molecular mechanism was not fully clarified. Consequently, objective of the present narrative review was to clarify the mechanistic role of VPN in AS. Most of pro-inflammatory cytokines released from macrophages are inhibited by the action of VPN via NF- κ B-dependent mechanism. VPN blocks monocyte adhesion and migration by inhibiting the expression of pro-inflammatory cytokines. As well, VPN is effective in reducing oxidative stress, a cornerstone in the pathogenesis of AS, through inhibition of NF- κ B and PDE1. VPN promotes plaque stability and prevent erosion and rupture of atherosclerotic plaque. In conclusion, VPN through mitigation of inflammatory and oxidative stress with plaque stability effects could be effective agent in the management of endothelial dysfunction through inhibition of atherosclerosis mediators.

Nanoparticles Mediated Salt Stress Resilience: A Holistic Exploration of Physiological, Biochemical, and Nano-omics Approaches - Abhishek Singh; Vishnu D. Rajput; Shreni Agrawal; Karen Ghazaryan; Tatiana Minkina; Abdel Rahman Mohammad Al Tawaha; Avnish Chauhan; Saglara S. Mandzhieva; Rupesh Kumar Singh; Marios Papadakis; Athanasios Alexiou (Reviews of Environmental Contamination and Toxicology, 2024)

Therapeutic Potential Effect of Glycogen Synthase Kinase 3 Beta (GSK-3β) Inhibitors in Parkinson Disease: Exploring an Overlooked Avenue - Areej Turkistani; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Ali K. Albuhadily; Athanasios Alexiou; Marios Papadakis; Mohamed M. Elfiky; Hebatallah M. Saad; Gaber El-Saber Batiha (Molecular Neurobiology, 2024)
Parkinson’s disease (PD) is a progressive neurodegenerative disease of the brain due to degeneration of dopaminergic neurons in the substantia nigra (SN). Glycogen synthase kinase 3 beta (GSK-3β) is implicated in the pathogenesis of PD. Therefore, the purpose of the present review was to revise the mechanistic role of GSK-3β in PD neuropathology, and how GSK-3β inhibitors affect PD neuropathology. GSK-3 is a conserved threonine/serine kinase protein that is intricate in the regulation of cellular anabolic and catabolic pathways by modulating glycogen synthase. Over-expression of GSK-3β is also interconnected with the development of different neurodegenerative diseases. However, the underlying mechanism of GSK-3β in PD neuropathology is not fully clarified. Over-expression of GSK-3β induces the development of PD by triggering mitochondrial dysfunction and oxidative stress in the dopaminergic neurons of the SN. NF-κB and NLRP3 inflammasome are activated in response to dysregulated GSK-3β in PD leading to progressive neuronal injury. Higher expression of GSK-3β in the early stages of PD neuropathology might contribute to the reduction of neuroprotective brain-derived neurotrophic factor (BDNF). Thus, GSK-3β inhibitors may be effective in PD by reducing inflammatory and oxidative stress disorders which are associated with degeneration of dopaminergic in the SN.

The therapeutic value of Myrtus communis L.: an updated review - Ali Esmail Al-Snafi; John Oluwafemi Teibo; Hazem M. Shaheen; Opeyemi Abigail Akinfe; Titilade Kehinde Ayandeyi Teibo; Numonde Emieseimokumo; Mohamed M. Elfiky; Hayder M. Al-kuraishy; Ali I. Al-Garbeeb; Athanasios Alexiou; Marios Papadakis; Hitham Alaa Mohammed Mahana; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Myrtus communis L. (Family: Myrtaceae) is naturally found in the western part of Asia, Southern Europe, and North Africa. It has been reportedly applied in pharmaceutical industry, traditional medicine, cosmetics, spices, and food. Pubmed, Google scholar, Web of Science, and Scopus were utilized to seek out relevant content concerning the therapeutic potential of M. communis . Subsequently, we conducted a review to identity noteworthy updates pertaining to M. communis . Myrtle berries, leaves, seeds, and essential oils are natural sources of several nutrients and bioactive compounds with marked health effects. The chemical analysis showed that M. communis contained oils, alkaloids, flavonoids, phenolics, coumarins, saponosides, tannins, quinines, and anthraquinones. A pharmacological investigation revealed that M. communis possessed anti-inflammatory, analgesic, antimicrobial, antiparasitic, antioxidant, antidiabetic, anticancer, antimutagenic, immunomodulatory, dermatological, cardiovascular, central nervous system, and gastrointestinal protective effects, among numerous other biological effects. This current review focused on the biochemical, pharmacological, therapeutic effects, and various biological activities of different parts of M. communis . It signifies that M. communis is a therapeutic plant with numerous applications in medicine and could be used as a drug isolate based on its safety and effectiveness.

Correction: Therapeutic potential of Lawsonia inermis Linn: a comprehensive overview - Gaber El‑Saber Batiha; John Oluwafemi Teibo; Hazem M. Shaheen; Benjamin Ayodipupo Babalola; Titilade Kehinde Ayandeyi Teibo; Hayder M. Al‑kuraishy; Ali I. Al‑Garbeeb; Athanasios Alexiou; Marios Papadakis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Therapeutic potential of Lawsonia inermis Linn: a comprehensive overview - Gaber El-Saber Batiha; John Oluwafemi Teibo; Hazem M. Shaheen; Benjamin Ayodipupo Babalola; Titilade Kehinde Ayandeyi Teibo; Hayder M. Al-kuraishy; Ali I. Al-Garbeeb; Athanasios Alexiou; Marios Papadakis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Lawsonia inerm is Linn, commonly known as henna, is a member of the Lythraceae family and has been found to contain a variety of compounds with both industrial and medicinal applications in its stem, bark, roots, flowers, and seeds. This report provides a comprehensive review of the bioactive components, pharmacological activities, pharmacokinetics, and pharmacological side effects of Lawsonia inermis . Relevant materials were gathered from Google Scholar, PubMed, Scopus, and Web of Science and reviewed for important properties and updates about the plant. Lawsonia inermis contains a variety of bioactive compounds, including flavonoids, coumarins, triterpenoids, steroids, xanthones, polyphenols, fatty acids, alkaloids, quinones, tannins, leucocyandin, epicatechin, catechin, and quercetin. The plant is been traditionally used to treat numerous conditions, including ulcers, bronchitis, lumbago, hemicrania, leukoderma, scabies, boils, ophthalmic disorders, hair loss, and jaundice. It has also been found to possess a range of pharmacological activities, including antioxidant, anti-inflammatory, analgesic, antiparasitic, hepatoprotective, antifungal, antitumor, wound healing, and hypoglycemic effects. The potential of Lawsonia inermis for various biological applications is promising, and further studies are needed to fully explore its therapeutic benefits for various diseases of public health. Concern advances in drug development could enable the characterization of various bioactive constituents and facilitate their development and application for the benefit of humanity.

The potential link between acromegaly and risk of acute ischemic stroke in patients with pituitary adenoma: a new perspective - Saud A. Alnaaim; Hayder M. Al-kuraishy; Mohammad Mitran Zailaie; Athanasios Alexiou; Marios Papadakis; Hebatallah M. Saad; Gaber El-Saber Batiha (Acta Neurologica Belgica, 2024)
Acromegaly is an endocrine disorder due to the excess production of growth hormone (GH) from the anterior pituitary gland after closed epiphyseal growth plates. Acromegaly is mainly caused by benign GH-secreting pituitary adenoma. Acute ischemic stroke (AIS) is one of the most common cardiovascular complications. It ranks second after ischemic heart disease (IHD) as a cause of disability and death in high-income countries globally. Thus, this review aimed to elucidate the possible link between acromegaly and the development of AIS. The local effects of acromegaly in the development of AIS are related to the development of pituitary adenoma and associated surgical and radiotherapies. Pituitary adenoma triggers the development of AIS through different mechanisms, particularly aneurysmal formation, associated thrombosis, and alteration of cerebral microcirculation. Cardiovascular complications and mortality were higher in patients with pituitary adenoma. The systemic effect of acromegaly-induced cardio–metabolic disorders may increase the risk for the development of AIS. Additionally, acromegaly contributes to the development of endothelial dysfunction (ED), inflammatory and oxidative stress, and induction of thrombosis that increases the risk for the development of AIS. Moreover, activated signaling pathways, including activator of transcription 3 (STAT3), nuclear factor kappa B (NF-κB), nod-like receptor pyrin 3 (NLRP3) inflammasome, and mitogen-activated protein kinase (MAPK) in acromegaly may induce systemic inflammation with the development of cardiovascular complications mainly AIS. Taken together, acromegaly triggers the development of AIS through local and systemic effects by inducing the formation of a cerebral vessel aneurysm, the release of pro-inflammatory cytokines, the development of oxidative stress, ED, and thrombosis correspondingly.

Unraveling the Endocannabinoid System: Exploring Its Therapeutic Potential in Autism Spectrum Disorder - Ankit Jana; Arnab Nath; Palash Sen; Swikriti Kundu; Badrah S. Alghamdi; Turki S. Abujamel; Muhammad Saboor; Chan Woon-Khiong; Athanasios Alexiou; Marios Papadakis; Mohammad Zubair Alam; Ghulam Md Ashraf (NeuroMolecular Medicine, 2024)
The salient features of autism spectrum disorder (ASD) encompass persistent difficulties in social communication, as well as the presence of restricted and repetitive facets of behavior, hobbies, or pursuits, which are often accompanied with cognitive limitations. Over the past few decades, a sizable number of studies have been conducted to enhance our understanding of the pathophysiology of ASD. Preclinical rat models have proven to be extremely valuable in simulating and analyzing the roles of a wide range of established environmental and genetic factors. Recent research has also demonstrated the significant involvement of the endocannabinoid system (ECS) in the pathogenesis of several neuropsychiatric diseases, including ASD. In fact, the ECS has the potential to regulate a multitude of metabolic and cellular pathways associated with autism, including the immune system. Moreover, the ECS has emerged as a promising target for intervention with high predictive validity. Particularly noteworthy are resent preclinical studies in rodents, which describe the onset of ASD-like symptoms after various genetic or pharmacological interventions targeting the ECS, providing encouraging evidence for further exploration in this area.

The potential therapeutic effect of phosphodiesterase 5 inhibitors in the acute ischemic stroke (AIS) - Raed AlRuwaili; Hayder M. Al-kuraishy; Mubarak Alruwaili; Amira Karam Khalifa; Athanasios Alexiou; Marios Papadakis; Hebatallah M. Saad; Gaber El-Saber Batiha (Molecular and Cellular Biochemistry, 2024)
Acute ischemic stroke (AIS) is a focal neurological disorder that accounts for 85% of all stroke types, due to occlusion of cerebral arteries by thrombosis and emboli. AIS is also developed due to cerebral hemodynamic abnormality. AIS is associated with the development of neuroinflammation which increases the severity of AIS. Phosphodiesterase enzyme (PDEs) inhibitors have neuro-restorative and neuroprotective effects against the development of AIS through modulation of the cerebral cyclic adenosine monophosphate (cAMP)/cyclic guanosine monophosphate (cGMP)/nitric oxide (NO) pathway. PDE5 inhibitors through mitigation of neuroinflammation may decrease the risk of long-term AIS-induced complications. PDE5 inhibitors may affect the hemodynamic properties and coagulation pathway which are associated with thrombotic complications in AIS. PDE5 inhibitors reduce activation of the pro-coagulant pathway and improve the microcirculatory level in patients with hemodynamic disturbances in AIS. PDE5 inhibitors mainly tadalafil and sildenafil improve clinical outcomes in AIS patients through the regulation of cerebral perfusion and cerebral blood flow (CBF). PDE5 inhibitors reduced thrombomodulin, P-selectin, and tissue plasminogen activator. Herein, PDE5 inhibitors may reduce activation of the pro-coagulant pathway and improve the microcirculatory level in patients with hemodynamic disturbances in AIS. In conclusion, PDE5 inhibitors may have potential roles in the management of AIS through modulation of CBF, cAMP/cGMP/NO pathway, neuroinflammation, and inflammatory signaling pathways. Preclinical and clinical studies are recommended in this regard. Graphical abstract

Zinc oxide nanoparticles influence on plant tolerance to salinity stress: insights into physiological, biochemical, and molecular responses - Abhishek Singh; Vishnu D. Rajput; Shivani Lalotra; Shreni Agrawal; Karen Ghazaryan; Jagpreet Singh; Tatiana Minkina; Priyadarshani Rajput; Saglara Mandzhieva; Athanasios Alexiou (Environmental Geochemistry and Health, 2024)

The probable role of tissue plasminogen activator/neuroserpin axis in Alzheimer’s disease: a new perspective - Naif H. Ali; Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Saud A. Alnaaim; Athanasios Alexiou; Marios Papadakis; Hebatallah M. Saad; Gaber El-Saber Batiha (Acta Neurologica Belgica, 2024)
Alzheimer’s disease (AD) is the most common type of dementia associated with amyloid beta (Aβ) deposition. Dysfunction of the neuronal clearance pathway promotes the accumulation of Aβ. The plasminogen-activating system (PAS) is controlled by various enzymes like tissue plasminogen activators (tPA). Neuronal tPA enhances the conversion of plasminogen to plasmin, which cleaves Aβ; this function is controlled by many inhibitors of PAS, including a plasminogen-activating inhibitor (PAI-1) and neuroserpin. Therefore, the objective of the present narrative review was to explore the potential role of tPA/neuroserpin in the pathogenesis of AD. PAI-1 activity is increased in AD, which is involved in accumulating Aβ. Progressive increase of Aβ level during AD neuropathology is correlated with the over-production of PAI-1 with subsequent reduction of plasmin and tPA activities. Reducing plasmin and tPA activities promote Aβ by reducing Aβ clearance. Neuroserpin plays a critical role in the pathogenesis of AD as it regulates the expression and accumulation of Aβ. Higher expression of neuroserpin inhibits the neuroprotective tPA and the generation of plasmin with subsequent reduction in the clearance of Aβ. These observations raise conflicting evidence on whether neuroserpin is neuroprotective or involved in AD progression. Thus, neuroserpin over-expression with subsequent reduction of tPA may propagate AD neuropathology. Graphical abstract

Does vitamin D protect or treat Parkinson’s disease? A narrative review - Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Hend Mostafa Selim; Athanasios Alexiou; Marios Papadakis; Walaa A. Negm; Gaber El-Saber Batiha (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Parkinson’s disease (PD) is a neurodegenerative brain disease (NBD) developed due to dopaminergic neuron loss in the substantia nigra (SN). Vitamin D (VD), VD receptor (VDR), and VD metabolites are highly expressed in the human brain and play a critical role in maintaining different brain functions. VDRs are highly expressed in the SN that regulates the activity of dopaminergic neurons and synaptic plasticity. VD exerts protective and therapeutic effects against the development of PD by modulating dopaminergic neurons of SN. VD reduces oxidative stress and neuroinflammation in PD because of its anti-inflammatory and antioxidant activities. Different studies revealed the protective effect of VD in the management of PD. However, the potential therapeutic effect of VD in well-established PD remains controversial. Therefore, this review aims to elucidate VD’s preventive and therapeutic roles in PD. In conclusion, VD deficiency is associated with increased PD risk, but VD supplementation in well-established PD plays little role.

Role of Brain Liver X Receptor in Parkinson’s Disease: Hidden Treasure and Emerging Opportunities - Saud A. Alnaaim; Hayder M. Al-Kuraishy; Athanasios Alexiou; Marios Papadakis; Hebatallah M. Saad; Gaber El-Saber Batiha (Molecular Neurobiology, 2024)
Parkinson’s disease (PD) is a neurodegenerative disease due to the degeneration of dopaminergic neurons (DNs) in the substantia nigra (SN). The liver X receptor (LXR) is involved in different neurodegenerative diseases. Therefore, the objective of the present review was to clarify the possible role of LXR in PD neuropathology. LXRs are the most common nuclear receptors of transcription factors that regulate cholesterol metabolism and have pleiotropic effects, including anti-inflammatory effects and reducing intracellular cholesterol accumulation. LXRs are highly expressed in the adult brain and act as endogenous sensors for intracellular cholesterol. LXRs have neuroprotective effects against the development of neuroinflammation in different neurodegenerative diseases by inhibiting the expression of pro-inflammatory cytokines. LXRs play an essential role in mitigating PD neuropathology by reducing the expression of inflammatory signaling pathways, neuroinflammation, oxidative stress, mitochondrial dysfunction, and enhancement of BDNF signaling. In conclusion, LXRs, through regulating brain cholesterol homeostasis, may be effectual in PD. Also, inhibition of node-like receptor pyrin 3 (NLRP3) inflammasome and nuclear factor kappa B (NF-κB) by LXRs could effectively prevent neuroinflammation in PD. Taken together, LXRs play a crucial role in PD neuropathology by inhibiting neuroinflammation and associated degeneration of DNs.

New insights on the potential effect of vinpocetine in Parkinson’s disease: one of the neglected warden and baffling topics - Hayder M. Al-kuraishy; Athanasios Alexiou; Marios Papadakis; Omnya Elhussieny; Hebatallah M. Saad; Gaber El-Saber Batiha (Metabolic Brain Disease, 2023)
Vinpocetine (VPN) is an ethyl apovincaminate that has anti-inflammatory and antioxidant effects by inhibiting the expression of nuclear factor kappa B (NF-κB) and phosphodiesterase enzyme 1 (PDE-1). VPN is used in the management of stroke, dementia, and other neurodegenerative brain diseases. VPN may be effective in treating Parkinson’s disease (PD). Therefore, this review aimed to clarify the mechanistic role of VPN in the management of PD. VPN has protective and restorative effects against neuronal injury by reducing neuroinflammation, and improvement of synaptic plasticity and cerebral blood flow. VPN protects dopaminergic neurons by reducing oxidative stress, lipid peroxidation, glutamate neurotoxicity, and regulation of Ca + 2 overloads. VPN can alleviate PD neuropathology through its anti-inflammatory, antioxidant, antiapoptotic and neurogenic effects. VPN through inhibition of PDE1 improves cyclic adenosine monophosphate (cAMP)/cyclic guanosine monophosphate (cGMP) signaling in the dopaminergic neurons of the substantia nigra (SN). VPN improves PD neuropathology through PDE1 inhibition with a subsequent increase of the cAMP/cGMP signaling pathway. Therefore, increasing cAMP leads to antioxidant effects, while augmentation of cGMP by VPN leads to anti-inflammatory effects which reduced neurotoxicity and development of motor severity in PD. In conclusion, this review indicated that VPN could be effective in the management of PD.

Morus alba: a comprehensive phytochemical and pharmacological review - Gaber El-Saber Batiha; Ali Esmail Al-Snafi; Mahdi M. Thuwaini; John Oluwafemi Teibo; Hazem M. Shaheen; Ayomide Peter Akomolafe; Titilade Kehinde Ayandeyi Teibo; Hayder M. Al-kuraishy; Ali I. Al-Garbeeb; Athanasios Alexiou; Marios Papadakis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Morus alba is a fast-growing shrub or medium-sized tree with a straight, cylindrical trunk. Medicinally, whole plants, leaves, fruits, branches, and roots have been employed. Google Scholar, PubMed, Scopus, and Web of Science were used to search for relevant material on the phytochemical components and pharmacologic and mechanism of action of the Morus alba . This was reviewed to assess important updates about Morus alba . The fruits of Morus alba have traditionally been used as an analgesic, anthelmintic, antibacterial, anti-rheumatic, diuretic, hypotensive, hypoglycemia, purgative, restorative, sedative tonic, and blood stimulant. Various plant parts were used as a cooling, sedating, diuretic, tonic, and astringent agent to treat nerve disorders. The plant contained tannins, steroids, phytosterols, sitosterol, glycosides, alkaloids, carbohydrates, proteins, and amino acids, as well as saponins, triterpenes, phenolics, flavonoids, benzofuran derivatives, anthocyanins, anthraquinones, glycosides, vitamins, and minerals. Previous pharmacological research identified antimicrobial, anti-inflammatory, immunological, analgesic, antipyretic, antioxidant, anti-cancer, antidiabetic, gastrointestinal, respiratory, cardiovascular, hypolipidemic, anti-obesity, dermatological, neurological, muscular, and protecting effects. This study looked at Morus alba ’s traditional uses, chemical components, and pharmacological effects.

A review of the bioactive components and pharmacological properties of Lavandula species - Gaber El-Saber Batiha; John Oluwafemi Teibo; Lamiaa Wasef; Hazem M. Shaheen; Ayomide Peter Akomolafe; Titilade Kehinde Ayandeyi Teibo; Hayder M. Al-kuraishy; Ali I. Al-Garbeeb; Athanasios Alexiou; Marios Papadakis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Lavandula species is a flowering plant that is common in Europe and across the Mediterranean. Lavender has many health benefits for humans. In addition to its use in herbal medicine, it is widely used in the fields of cosmetics, perfumes, foods, and aromatherapy. Google Scholar, PubMed, Scopus, and Web of Science were used to search for relevant material on the phytochemical ingredients, the pharmacologic effects of the ingredients, and the mechanism of action of the Lavandula species identified. These materials were reviewed in order to have access to important updates about the Lavandula species. Lavender as referred to in English contains essential oils, anthocyanins, phytosterols, sugars, minerals, coumaric acid, glycolic acid, valeric acid, ursolic acid, herniarins, coumarins, and tannins. It has been used to treat colic and chest ailments, worrisome headaches, and biliousness, and in cleaning wounds. It has antifungal, antibacterial, neurologic, antimicrobial, anti-parasitic, anti-diabetic, and analgesic effects among others. Lavandula species has prospects for various biological applications, especially with its dermatological application. Advances in drug development would enable characterization of various bioactive constituents; thus, its development and application can have a more positive impact on humanity. Here, we highlighted updated information on the history, distribution, traditional uses, phytochemical components, pharmacology, and various biological activities of Lavandula species.

Synonymous Codon Variant Analysis for Autophagic Genes Dysregulated in Neurodegeneration - Rekha Khandia; Megha Katare Pandey; Igor Vladimirovich Rzhepakovsky; Azmat Ali Khan; Athanasios Alexiou (Molecular Neurobiology, 2023)

The phytochemical profiling, pharmacological activities, and safety of malva sylvestris: a review - Gaber El-Saber Batiha; Stephano Tambo Tene; John Oluwafemi Teibo; Hazem M. Shaheen; Oyerinde Samson Oluwatoba; Titilade Kehinde Ayandeyi Teibo; Hayder M. Al-kuraishy; Ali I. Al-Garbee; Athanasios Alexiou; Marios Papadakis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Malva sylvestris is a plant commonly found in Europe, Asia, and Africa. The leaves and flowers of this plant have been used for centuries in traditional medicine to treat various ailments such as cough, cold, diarrhoea, and constipation. Google Scholar, PubMed, Scopus, and Web of Science were used to search for relevant material on the phytochemical profiling and pharmacologic activities of Malva sylvestris . The techniques used in phytochemical profiling and the pharmacologic activity of each compound were extracted from the included studies, including in vitro, in vivo, and clinical studies. The phytochemical analysis of Malva sylvestris revealed that the leaves and flowers are the most commonly used parts of the plant and contain various bioactive compounds such as flavonoids, mucilages, terpenoids, phenol derivatives, coumarins, sterols, tannins, saponins, and alkaloids. These phytochemicals are responsible for the many pharmacological activities of Malva sylvestris, such as anti-inflammatory, antimicrobial, hepatoprotective, laxative, antiproliferative and antioxidant properties. This review has presented an overview of the antinociceptive and anti-inflammatory activities and the cytotoxic effects of Malva sylvestris on different types of cancer cells. It has also summarised the work on developing copper oxide nanoparticles using Malva sylvestris leaf extract and its potential use in food and medicine. This review aims to highlight the traditional uses, phytochemistry, pharmacological activities, and safety of Malva sylvestris .

Commiphora myrrh: a phytochemical and pharmacological update - Gaber El-Saber Batiha; Lamiaa Wasef; John Oluwafemi Teibo; Hazem M. Shaheen; Ali Muhammad Zakariya; Opeyemi Abigail Akinfe; Titilade Kehinde Ayandeyi Teibo; Hayder M. Al-kuraishy; Ali I. Al-Garbee; Athanasios Alexiou; Marios Papadakis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
Medicinal plants have a long track record of use in history, and one of them is Commiphora myrrh which is commonly found in the southern part of Arabia, the northeastern part of Africa, in Somalia, and Kenya. Relevant literatures were accessed via Google Scholar, PubMed, Scopus, and Web of Science to give updated information on the phytochemical constituents and pharmacological action of Commiphora myrrh . It has been used traditionally for treating wounds, mouth ulcers, aches, fractures, stomach disorders, microbial infections, and inflammatory diseases. It is used as an antiseptic, astringent, anthelmintic, carminative, emmenagogue, and as an expectorant. Phytochemical studies have shown that it contains terpenoids (monoterpenoids, sesquiterpenoids, and volatile/essential oil), diterpenoids, triterpenoids, and steroids. Its essential oil has applications in cosmetics, aromatherapy, and perfumery. Research has shown that it exerts various biological activities such as anti-inflammatory, antioxidant, anti-microbial, neuroprotective, anti-diabetic, anti-cancer, analgesic, anti-parasitic, and recently, it was found to work against respiratory infections like COVID-19. With the advancement in drug development, hopefully, its rich phytochemical components can be explored for drug development as an insecticide due to its great anti-parasitic activity. Also, its interactions with drugs can be fully elucidated. This review highlights an updated information on the history, distribution, traditional uses, phytochemical components, pharmacology, and various biological activities of Commiphora myrrh . Graphical abstract Graphical summary of the phytochemical and pharmacological update of Commiphora myrrh

Bioactive compounds, pharmacological actions and pharmacokinetics of Cupressus sempervirens - Gaber El-Saber Batiha; John Oluwafemi Teibo; Hazem M. Shaheen; Opeyemi Abigail Akinfe; Aya Ahmed Awad; Titilade Kehinde Ayandeyi Teibo; Athanasios Alexiou; Marios Papadakis (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)
The roles of plants and its products in all forms of life cannot be overemphasized. The medicinal products from plant are phytochemicals, drugs, food supplements, beauty products, etc. In ethnomedicine, leaves, fruits, stem, bark, root and fluids from plants are used in the cure, management and prevention of several diseases. Cupressus sempervirens , sometimes called Italian or Mediterranean cypress, is found in subtropical Asia, North America and eastern Mediterranean region. Pharmacological investigations of Cupressus sempervirens showed biological properties such as aromatherapeutic, antiseptic, astringent, balsamic or anti-inflammatory, astringent, antiperspirant, diuretic and antispasmodic. Chemical analysis of Cupressus sempervirens gives phytochemicals like monoterpenes, diterpenes, flavonoid glycosides and bioflavonoids. The current review highlights interactions, conventional uses and biological actions of Cupressus sempervirens plant and plant products.

Treatments against Polymorphosal discrepancies in Glioblastoma Multiforme - Nobendu Mukerjee; Swastika Maitra; Subhradeep Roy; Shaswata Modak; Mohammad Mehedi Hasan; Biswajit Chakraborty; Arabinda Ghosh; Asmita Ghosh; Mohammad Amjad Kamal; Abhijit Dey; Ghulam Md Ashraf; Sumira Malik; et al. (Metabolic Brain Disease, 2023)

Ursolic acid and SARS-CoV-2 infection: a new horizon and perspective - Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Walaa A. Negm; Athanasios Alexiou; Gaber El-Saber Batiha (Inflammopharmacology, 2022)

RETRACTED ARTICLE: COVID-19 diagnostic methods in developing countries - Md. Maniruzzaman; Md. Missile Islam; Md. Hazrat Ali; Nobendu Mukerjee; Swastika Maitra; Mohammad Amjad Kamal; Arabinda Ghosh; Melvin A. Castrosanto; Athanasios Alexiou; Ghulam Md. Ashraf; Priti Tagde; Md. Habibur Rahman (Environmental Science and Pollution Research, 2022)

Isolation, characterization and in vitro antioxidant activity screening of pure compound from black pepper (Piper nigrum) - Murshida Mollik; Md. Habibur Rahman; Majed Al-Shaeri; Ghulam Md. Ashraf; Athanasios Alexiou; Md. Abdul Gafur (Environmental Science and Pollution Research, 2022)

Effect of Cliothosa aurivilli on Paclitaxel-induced Peripheral Neuropathy in Experimental Animals - Varnita Karmakar; Firdous Sayeed Mohammad; Saleh S. Baeesa; Athanasios Alexiou; S. R. Sivakumar; Ghulam Md Ashraf (Molecular Neurobiology, 2022)

Niclosamide for Covid-19: bridging the gap - Hayder M. Al-kuraishy; Ali I. Al-Gareeb; Khalid J. Alzahrani; Athanasios Alexiou; Gaber El-Saber Batiha (Molecular Biology Reports, 2021)

Role of GTPases in the Regulation of Mitochondrial Dynamics in Alzheimer’s Disease and CNS-Related Disorders - Athanasios Alexiou; Georgia Soursou; Stylianos Chatzichronis; Ermis Gasparatos; Mohammad Amjad Kamal; Nagendra Sastry Yarla; Asma Perveen; George E. Barreto; Ghulam Md Ashraf (Molecular Neurobiology, 2019)

Circulating progenitor cells: a comparison of patients with glioblastoma or meningioma - George A. Alexiou; George Vartholomatos; Achilleas Karamoutsios; Anna Batistatou; Athanasios P. Kyritsis; Spyridon Voulgaris (Acta Neurologica Belgica, 2013)